Admission Rates and Care Pathways in Patients with Atrial Fibrillation during the COVID-19 Pandemic – Insights from the German-wide Helios Hospital Network - Ueberham, Laura (Eur Heart J Qual Care Clin Outcomes, 2021)
INTRODUCTION: Several reports indicate lower rates of emergency admissions in the cardiovascular sector and reduced admissions of patients with chronic diseases during the COVID-19 pandemic. The aim of this study was therefore to evaluate numbers of admissions in incident and prevalent atrial fibrillation and flutter (AF) and to analyze care pathways in comparison to 2019. METHODS: A retrospective analysis of claims data of 74 German Helios hospitals was performed to identify consecutive patients hospitalized with a main discharge diagnosis of AF. A study period including the start of the German national protection phase (13th March 2020 to 16th July 2020) was compared to a previous year control cohort (15th March 2019 to 18th July 2019), with further sub-division into early and late phase. Incidence rate ratios (IRR) were calculated. Numbers of admission per day (A/day) for incident and prevalent AF and care pathways including readmissions, numbers of transesophageal echocardiogram (TEE), electrical cardioversion (CV) and catheter ablation (CA) were analyzed. RESULTS: During the COVID-19 pandemic, there was a significant decrease of total AF admissions both in the early (44.4 vs. 77.5 A/day, IRR 0.57 [95% CI 0.54–0.61], p < 0.01) and late phase (59.1 vs. 63.5 A/day, IRR 0.93 [95% CI 0.90–0.96], p < 0.01), length of stay was significantly shorter (3.3 ± 3.1 nigths vs. 3.5 ± 3.6 nigths, p < 0.01), admissions were more frequently in high volume centers (77.0% vs. 75.4%, p = 0.02) and frequency of readmissions was reduced (21.7% vs. 23.6%, p < 0.01) compared to the previous year. Incident AF admission rates were significantly lower both in the early (21.9 admission per day vs. 41.1 A/day, IRR 0.53 [95% CI 0.48 − 0.58]) and late phase (35.5 vs. 39.3 A/day, IRR 0.90 [95% CI 0.86 − 0.95]), whereas prevalent admissions were only lower in the early phase (22.5 vs 36.4 A/day IRR 0.62 [95% CI 0.56 − 0.68]), but not in the late phase (23.6 vs. 24.2 A/day IRR 0.97 [95% CI 0.92 − 1.03]). Analysis of care pathways showed reduced numbers of TEE during the early phase (34.7% vs. 41.4%, OR 0.74 [95% CI 0.64 − 0.86], p < 0.01), but not during the late phase (39.9% vs. 40.2%, OR 0.96 [95% CI 0.88 − 1.03], p = 0.26). Numbers of CV were comparable during early (40.6% vs. 39.7%, OR 1.08 [95% CI 0.94 − 1.25], p = 0.27) and late phase (38.6% vs. 37.5%, OR 1.06 [95% CI 0.98 − 1.14], p = 0.17), compared to the previous year, respectively. Numbers of CA were comparable during the early phase (21.6% vs. 21.1%, OR 0.98 [95% CI 0.82 − 1.17], p = 0.82) with a distinct increase during the late phase (22.9% vs. 21.5%, OR 1.05 [95% CI 0.96–1.16], p = 0.28). CONCLUSION: During the COVID-19 pandemic, AF admission rates declined significantly, with a more pronounced reduction in incident than in prevalent AF. Overall AF care was maintained during early and late pandemic phase with only minor changes, namely less frequent use of TEE. Confirmation of these findings in other study populations as well as identification of underlying causes are required to ensure optimal therapy in patients with AF during the COVID-19 pandemic.